Transnational communism across the Americas - Becker, Marc (Professor of history) (University of Illinois Press, 2023)
"Did Latin American communists have stronger roots in the worldwide movement or in the historical developments of their own countries? This collection uses a transnational lens to examine the relationships of the region's local parties with each other, international counterparts, and outside groups dedicated to anti-imperialism, women's rights, and other causes. Part One's essays explore the era from the Bolshevik Revolution through 1943. Topics include the failed connection between Mexican communists and the Comintern, Black migrant workers and the Caribbean labor movement, race relations in Cuba, Latin American communists in the USSR, and Luís Carlos Prestes and the Brazilian Communist Party. Part Two focuses on the Cold War years to look at Soviet peace activism networks in Latin America, Guatemala's communist women before the 1954 coup, Puerto Rico's communist party, transnational student groups, and international influences on Salvadoran guerrillas. Insightful and expert, Transnational Communism across the Americas illuminates the various Latin American communist parties and their milieus, programs, and policies"--